Surgical Site Infections after Free Flap Breast Reconstruction: An Analysis of 2,899 Patients from the ACS-NSQIP Datasets - Chung, Cyndi U.; Wink, Jason D.; Nelson, Jonas A.; Fischer, John P.; Serletti, Joseph M.; Kanchwala, Suhail K. (Journal of Reconstructive Microsurgery, 2015)
Background Surgical site infections (SSIs) are a costly complication, resulting in lower patient satisfaction and higher health care expenditures. Incidence varies widely in the literature by surgery type, yet few studies focus exclusively on autologous breast reconstruction, an increasingly common surgery. The aim of this study is to identify risk factors for SSIs in free flap breast reconstruction using the National Surgical Quality Improvement Program Database (NSQIP).Methods Patients undergoing breast reconstruction with any flap type were identified by Current Procedural Terminology codes in the NSQIP database. Patients with superficial or deep SSIs within 30 days of surgery were compared with controls by univariate analysis and multivariate logistic regression across various characteristics.Results Overall, 2,899 patients undergoing autologous reconstruction were identified. Of these, 143 (4.9%) patients developed SSIs. Those who developed wound complications were more likely smokers (18.2 vs. 8.4%, p < 0.001) and diabetics (9.8 vs. 3.4%, p < 0.001) with hypertension (38.2 vs. 25.4%, p < 0.001) and pulmonary (4.5 vs. 1.3%, p = 0.01) history. SSIs occurred in patients with higher American Society of Anesthesiologists (p = 0.003) and the World Health Organization obesity (p < 0.001) classes. On multivariate regression, SSIs were significantly associated with smoking (odds ratio [OR] = 3.59, p < 0.001) and hypertension (OR = 1.86, p = 0.03).Conclusions This study demonstrates that patients who are active smokers or have hypertension are at the highest risk for SSIs. Preoperative identification and tailored postoperative management of these patients may decrease the incidence of this complication.
Keywords: breast reconstruction; risk factor; wound complication; surgical site infection; plastic surgery